2014
DOI: 10.1080/10807039.2013.862111
|View full text |Cite
|
Sign up to set email alerts
|

A Fuzzy Logic Approach to Assess, Manage, and Communicate Carcinogenic Risk

Abstract: A prospective approach to addressing carcinogen risk assessment is presented. Fuzzy reasoning is used to assess carcinogenic risk, characterize it, and control it. The approach is inspired by fuzzy control inference that deploys linguistic intelligence as input to a system described numerically through membership functions. Fuzzy-based reasoning to estimate carcinogenic risk provides several advantages as discussed here. The fuzzy reasoning approach has more capabilities than traditional models in dealing with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Fuzzy set theory has been applied to quantify uncertainty in risk assessment (Arunraj et al., 2013; Kentel & Aral, 2005), and it allows the utilization of incomplete information when there is insufficient data to generate probability distributions for the parameters of the random variables of the risk equation (Kentel & Aral, 2005). Moreover, fuzzy‐based approaches are often the method of choice for handling uncertainties, including analyzing soft factors that are difficult to quantify (Loh et al., 2020; Matbouli et al., 2014). Consequently, fuzzy logic and expert judgments are widely used in several operational risk assessment studies such as in autonomous underwater vehicles (Brito & Dawson, 2020; Loh et al., 2020), in inland waterways (Martins et al., 2020), in nuclear power plants (Rastogi & Gabbar, 2013), and oil and gas industry (Mun, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Fuzzy set theory has been applied to quantify uncertainty in risk assessment (Arunraj et al., 2013; Kentel & Aral, 2005), and it allows the utilization of incomplete information when there is insufficient data to generate probability distributions for the parameters of the random variables of the risk equation (Kentel & Aral, 2005). Moreover, fuzzy‐based approaches are often the method of choice for handling uncertainties, including analyzing soft factors that are difficult to quantify (Loh et al., 2020; Matbouli et al., 2014). Consequently, fuzzy logic and expert judgments are widely used in several operational risk assessment studies such as in autonomous underwater vehicles (Brito & Dawson, 2020; Loh et al., 2020), in inland waterways (Martins et al., 2020), in nuclear power plants (Rastogi & Gabbar, 2013), and oil and gas industry (Mun, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Climate is a consistent phenomenon, information concentrated, dynamic and random process [1]. The parameters required to anticipate climate are colossally intricate with the end goal that there is a vulnerability in forecast notwithstanding for a brief period [2].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2008) applied a similar approach to assessing the health-impact risk from air pollution. Matbouli et al (2014) reported the use of fuzzy logic in the context of prospective assessment of cancer risks.…”
Section: Expressing Uncertainty Using Possibilitymentioning
confidence: 99%